Porosity Study of Hybrid Silica Mesostructure in Aluminium Oxide Membrane Columnar by Cyclic Voltammetry Method - Jalil, M.N.; Zaki, H.M.; Dryfe, R.A.W.; Anderson, M.W. (Journal of Science and Technology, 2011)
Silica mesostructure has been grown within with a porous aluminium oxide membrane columnar material (hybrid-AOM). This was prepared using a sol-gel technique with Pluronic P123 triblock copolymer as the structure-directing agent and tetraethyl orthosilicate as the inorganic source. The porosity of the hybrid-AOM after ethanol extraction was calculated from the cyclic voltammetry response of a neutral probe (FcMeOH), using Randles-SevÄik equation.